Random telegraph noise characteristic of nonvolatile resistive random access memories based on optical interference principle - Qin, Sichen; Zhang, Guiquan; Zhang, Jia-Wei; Zhao, Yu; Song, Chen; Emonds, Yannick; Fröning, Holger (Japanese journal of applied physics, 2024)
The influence of random telegraph noise (RTN) could reduce the reading margin, which would cause computational errors in data recognition. This paper proposes a current sensor based on the principle of optical fiber interference, which can avoid the interference generated during the RTN testing process and improve the accuracy due to its passive characteristics. In this study, a hafnium oxide based memristor was fabricated, the switching voltages of Cu and TiN as the top electrodes are 0.2 V and 0.15 V, respectively. In addition, the RTN spectral density of the two device structures in LRS increases from 10−5 to 10−1 A2 Hz−1 and from 10−5 to 101 A2 Hz−1 with increasing applied voltage. While the RTN in high resistance state is independent of the applied voltage. Furthermore, based on the analysis of the experimental data, the generation mechanism of the RTN is attributed to local defects and the capture or emission of carriers by traps.